2019
DOI: 10.1097/mjt.0000000000000696
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Drug Use for Onychomycosis

Abstract: Background: Onychomycoses are fungal nail infections affecting predominantly toenails, and mainly caused by dermatophyte fungi, molds and some Candida species. Nail infections can be mild with purely cosmetic implications, but they can also negatively influence quality of life. The deep-seated nature of fungi within the nail plate, prolonged treatment, poor patient adherence, frequent recurrences, and development of resistance to various antimicrobial agents make onychomycosis difficult to successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 42 publications
0
20
0
4
Order By: Relevance
“…The condition, if left untreated, may cause discomfort, pain, paresthesia, nail deformities such as transverse over-curvature, difficulties in trimming thick nail plates, difficulties in fitting shoes, and low self-esteem [ 7 , 9 , 14 , 37 , 53 , 78 , 89 ]. In addition, onychomycosis can be unsightly and socially embarrassing (especially for females) and may have an adverse affect on quality of life [ 4 , 6 , 7 , 90 - 92 ].…”
Section: Complicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…The condition, if left untreated, may cause discomfort, pain, paresthesia, nail deformities such as transverse over-curvature, difficulties in trimming thick nail plates, difficulties in fitting shoes, and low self-esteem [ 7 , 9 , 14 , 37 , 53 , 78 , 89 ]. In addition, onychomycosis can be unsightly and socially embarrassing (especially for females) and may have an adverse affect on quality of life [ 4 , 6 , 7 , 90 - 92 ].…”
Section: Complicationsmentioning
confidence: 99%
“…Currently, oral terbinafine (< 25kg, 125mg once daily; 25 to 35kg, 187.5mg once daily; > 35mg, 250mg once daily) is the drug of choice for the treatment of onychomycosis [ 39 , 53 , 62 , 88 , 100 , 101 ]. Adverse events include headaches, taste disturbance, dermatitis, anorexia, vomiting, epigastric pain, diarrhea, drug-to-drug interactions and, rarely, depression, neutropenia, hepatic dysfunction, and Steven-Johnson syndrome [ 4 , 17 , 53 , 81 ]. Generally, continuous terbinafine treatment has similar efficacy as pulse terbinafine treatment although some studies have shown superiority of continuous versus pulsed terbinafine treatment for toenail onychomycosis [ 102 ].…”
Section: Treatmentmentioning
confidence: 99%
See 3 more Smart Citations